Siri Pettersen - Subverting Reality through Fantasy - Cristina VIȘOVAN (Studia Universitatis Babeş-Bolyai. Philologia, 2023)
Siri PETTERSEN (born 1971) is an acclaimed Norwegian fantasy writer who has managed to challenge the Norwegian Publishing Houses’ perception about this genre. Endowed with a vivid imagination, she developed from early on a sense for creating stories which allowed her to experience fantastic realms as a means of escaping an injudicious reality whose rules Pettersen constantly broke as part of a role-play group of fantasy enthusiasts.